Analisis Peningkatan Kinerja Karyawan Puskesmas melalui Perbaikan Fasilitas Kantor, Motivasi Kerja, dan Disiplin Kerja - Adiba, Aila Adiba (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2025)
This study aims to determine the effect of work facilities, work motivation and work discipline on employee performance. In achieving these goals, researchers use explanatory research with a quantitative approach. The sampling technique used was a saturated sample. The researchers obtained a sample of 42 respondents who were employees at the Jasinga Health Center, Bogor. Data collection was carried out using a questionnaire which was then processed using the SPSS 25 analysis tool, then the data was processed using statistical techniques of multiple linear regression analysis. The results showed that office facilities had a positive and significant effect on employee performance, work motivation had a positive and significant effect on employee performance and work discipline had a positive and significant effect on employee performance. Partially, the results obtained are that there is a significant positive effect on office facilities on employee performance, work motivation has a positive and significant effect on employee performance and work discipline has a positive and significant effect on employee performance.